Detection of Enhanced In Vivo Platelet α-Granule Release in Different Patient Groups - Comparison of β-Thromboglobulin, Platelet Factor 4 and Thrombospondin Assays - Lane, D A; Ireland, H; Wolff, S; Ranasinghe, E; Dawes, J (Thrombosis and Haemostasis, 1984)
During the platelet release reaction β-thromboglobulin (βTG), platelet factor 4 (PF4) and thrombospondin (TSP) are released from the platelet into plasma and assays of these proteins can be used to monitor in vivo platelet activation. We have assessed their relative merits as markers of the in vivo platelet α-granule release reaction in a number of patient groups which have previously been shown to have elevated plasma βTG and/or PF4 levels. It is concluded that in diseases or conditions not complicated by its reduced clearance, βTG is the most sensitive marker of in vivo platelet α-granule release. However, the TSP assay may be the least ambiguous when monitoring the platelet α-granule release reaction in patients with renal failure who are undergoing haemodialysis with heparin anticoagulation. Under these circumstances plasma βTG, but not PF4 or TSP, levels are elevated because of impaired renal catabolism, and the presence of a heparin-releasable reservoir of PF4 on the endothelium complicates the use of the PF4 assay. In liver failure none of these assays may accurately reflect platelet α-granule release because of impaired hepatic or renal elimination of the proteins.
Keywords: β-thromboglobulin; Platelet factor 4; Thrombospondin